Investigation of Axial Strengthened Reinforced Concrete Columns under Lateral Blast Loading - Mohammad Esmaeilnia Omran; Somayeh Mollaei (Shock and Vibration)
Different factors can affect blast response of structural components. Hence, experimental tests could be the best method for evaluating structures under blast loading. Therefore, an experimental explosion loading has been done on RC members by the authors. Four RC components, with identical geometry and material, with and without axial load were imposed to air blast. Observed data of the members’ response under blast loading was used for validation of finite element modeling process using ABAQUS software. With respect to complexity, limitations, and high costs of experimental tests, analytical studies and software modeling can be good alternatives. Accordingly, in this paper, the behavior of 6 different models of normal and strengthened RC columns under blast loading was evaluated using ABAQUS. Strengthening configurations considered here were designed for enhancing axial capacity of RC columns. Therefore, we can investigate the effectiveness of axial strengthening of column on its blast resistance capacity and residual axial strength. The considered strengthening methods were different steel jacket configurations including steel angle, channel, and plate sections. The results showed that retrofitting significantly improves blast performance of the columns. Moreover, residual strength capacity of the columns strengthened with steel channel is higher than the other models.